A brief review and comparative evaluation of nanofluid application in solar parabolic trough and flat plate collectors. (November 2022) - Bamisile, Olusola; Cai, Dongsheng; Adun, Humphrey; Adedeji, Michael; Dagbasi, Mustafa; Dika, Ferdinard; Huang, Qi
Abstract: The mixture of nanoparticles with base fluid for heat transfer fluid's performance enhancement has received wide research attention recently. These nanofluids have been proposed by researchers as a better alternative in different thermal systems. However, the detailed comparison of these fluids is limited in the existing literature. Therefore, in this paper, a detailed parametric comparison of mono/hybrid nanofluids with other fluids' applications in solar thermal collectors is presented. Specifically, the flat plate and solar parabolic trough collectors are considered within the scope of this study. While the flat plate collectors are modeled for low-temperature applications, the parabolic trough collectors are considered for high-temperature applications. Five nanofluids with different nanoparticles, namely; Al2 O3, SiO 2, CuO, Al2 O3 -ZnO, and Al2 O3 -Fe are compared with four normal fluids (water, salt (7NaNO 3 _40NaNO 2 _53KNO2 ), Therminol_VP1, and Dowtherm_Q). From the energy/exergy efficiencies and useful energy output results of this study, the nanofluids had a better performance when applied in the flat plate collectors and parabolic trough collectors. Also, the working fluids with higher temperature output had lower energy efficiencies and useful energy output. Hence, the base (normal) fluids are more suitable for some specific temperature applications in a flat plate and parabolic trough collectors.